2009
DOI: 10.1177/0192623309339503
|View full text |Cite
|
Sign up to set email alerts
|

Occult Cardiotoxicity—Toxic Effects on Cardiac Ischemic Tolerance

Abstract: The outcome of cardiac ischemic events depends not only on the extent and duration of the ischemic stimulus but also on the myocardial intrinsic tolerance to ischemic injury. Cardiac ischemic tolerance reflects myocardial functional reserves that are not always used when the tissue is appropriately oxygenated. Ischemic tolerance is modulated by ubiquitous signal transduction pathways, transcription factors and cellular enzymes, converging on the mitochondria as the main end effector. Therefore, drugs and toxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 226 publications
(306 reference statements)
1
20
0
1
Order By: Relevance
“…We therefore concluded that ischemia tolerance is reduced in uremia [14,15]. There is growing evidence that the outcome of cardiac ischemic events depends not only on the extent and duration of the ischemic stimulus but also on the myocardial intrinsic tolerance to ischemic injury [30,31,32]. In line with our previous results [14,15] an increased area of myocardial necrosis was reproducible in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…We therefore concluded that ischemia tolerance is reduced in uremia [14,15]. There is growing evidence that the outcome of cardiac ischemic events depends not only on the extent and duration of the ischemic stimulus but also on the myocardial intrinsic tolerance to ischemic injury [30,31,32]. In line with our previous results [14,15] an increased area of myocardial necrosis was reproducible in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Very little is known on the possible unwanted effect of medications on the ischemic heart and endogenous cardioprotection, which may result in a latently developing cardiotoxicity (Golomb et al, 2009), and which is now termed as "hidden cardiotoxicity." Hidden cardiotoxicty of a medication may not be seen in the healthy heart but may manifest in only the ischemic heart as an increased tissue injury due to an increased sensitivity to an ischemic challenge or a decreased capability to adapt to an ischemic challenge.…”
Section: Effects Of Concomitant Medications Used Tomentioning
confidence: 99%
“…Some xenobiotics may have little direct effect on the cardiovascular system but may elicit “toxicity” by complicating or exacerbating pre-existing cardiovascular disease (Feenstra et al 1999; Golomb et al 2007; Golomb et al 2009). …”
Section: Manifestations Of Cardiovascular Toxicitymentioning
confidence: 99%